Singing the Song Indonesia Raya as a Form of National Commitment in Realizing Nationalism : Review of Hadith About Songs and Music - Ahmad Ghozali, Perdamaian Hsb, Syahruddin Srg, Rahman (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This article examines the singing of the national anthem 'Indonesia Raya' as a representation of the spirit of nationalism associated with the hadith of the Prophet. This topic is important to study because singing the song 'Indonesia Raya' is considered by some people to be illegal or even haram. Singing the song 'Indonesia Raya' does not weaken religious beliefs. Rather, it is an expression of love for the homeland towards Indonesia. Therefore, it is necessary to provide a legal explanation for singing the song 'Indonesia Raya' through the contextualization approach of the Prophet's hadith. This study uses a qualitative approach with data collection techniques through literature study. The results of this study indicate that song (music) has been practiced by the people at the time of the Prophet. For example, a woman who played the duff (tambourine) when the Prophet returned from war. Seeing the incident the prophet did not forbid it. Then most of the scholars allow chanting (music) as long as there is no element of disobedience in it. Up to this point, the actual prohibition of music lies not in the singing aspect, but in the accompanying activities (ikhtilath), which can lead to disobedience. In the context of singing the song 'Indonesia Raya' there is no element of disobedience in it. The song 'Indonesia Raya' was created as a symbol of love for the homeland. The lyrics are not negatively charged and are sung in formal and sacred situations.